Comparative cohorts of retinopathy of prematurity outcomes of differing oxygen saturation: real-world outcomes. Issue 1 (8th March 2021) - Choo, May May; Grigg, John; Barnes, Elizabeth H; Khaliddin, Nurliza; Kamalden, Tengku Ain; Ahmad Kamar, Azanna; Choo, Yao Mun; Lim, Chin Theam; Martin, Frank Joseph
Abstract : Objective: An ongoing third epidemic of retinopathy of prematurity (ROP) is contributed largely by developing nations. We describe a cohort of infants in a single neonatal unit where two limits of oxygen saturation were administered, to show real-world outcomes from trend in neonatology for higher oxygen to improve survival. Methods and analysis: This retrospective, comparative study of prospectively collected data in an ROP screening programme included infants indicated by gestational age ≤32 weeks, birth weight <1501 g, ventilation for 7 days or requiring oxygen >1 month, who underwent dilated fundoscopic examination from age 4 weeks, every 2 weeks until full retinal vascularisation. Infants with ROP were examined weekly and treated where indicated. Data were divided into two epochs. Epoch 1 oxygen saturation targets were [88–92%], epoch 2 targets [90–95% (99%)] with allowance of increase to 20% for several hours after procedures. Outcome measures included development of ROP, treatment, mortality, sepsis and intraventricular haemorrhage. Results: A total of 651 infants underwent examination between 2003 and 2016. The incidence of ROP in epoch 1 was 29.1% and epoch 2 was 29.3% (p=0.24). ROP progression doubled in epoch 2 (5 vs 11%, p=0.006), proportion of cases treated halved (14% vs 6%, p=0.0005), sepsis was halved (78.5% vs 41.2%, p<0.0001) and intraventricular haemorrhage doubled (20.2% vs 43.8%, p=0.0001) in epoch 2. Mortality was 4% and 0% in epochs 1 and 2, respectively. Conclusion: Incidence of ROP did not differ, although ROP cases that worsened doubled with higher oxygen targets. ROP cases requiring treatment decreased, as did sepsis and mortality. Intraventricular haemorrhage cases doubled.